Design and simulation of interdigitated electrode for Graphene-SnO2 sensor on acetone gas - Nur Hikmah; Huzein Fahmi Hawari; Monika Gupta (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This paper presents the design and simulation of interdigitated electrode for graphene-SnO2 sensor on acetone gas. This study focuses on designing and simulating a sensor platform based on IDE with different configuration parameters to obtain the most ideal and efficient layout concerning sensitivity. Eventhough the sensor platform can be easily fabricated by using photolithography, screen-printing and other methods, the simulation is preferable as it provides low cost, secure and quick analysis tools with required sensitivity analysis. The design is important before developing a hybrid gas sensor based on metal oxide and graphene to detect acetone for diabetic mellitus at room temperature. IDE is one of the sensor platforms which provide simplicity, miniaturization and offers an economical mass-fabrication as an alternative to large systems for a sensor. The sensitivity of this IDE can be improved by altering the parameters of the IDE configuration. Herein, COMSOL Multiphysics® 5.4 software is used for simulation where the IDE-based sensor is constructed, and the electrical field is simulated with dependence on several parameters such as width, gap, finger's number and thickness of the electrode. The electrical field that is generated by the simulation results were analyzed and discussed to find the ideal design with the highest sensitivity. From the simulation, it was found that the optimum sensitivity with electrical field of 58808 V/m was the design of IDE configuration with 14 fingers, 0.15 mm spacing size between fingers, 0.15 mm width of the finger and 0.7mm thickness of fingers and electrode.